Fine Mapping of Two Interacting Loci for Transmission Ratio Distortion in Rice (Oryza sativa L.) - Zhang, Chaopu; Wang, Jilin; Xiao, Xiongfeng; Wang, Dianwen; Yuan, Zhiyang; Zhang, Xiaodan; Sun, Wenqiang; Yu, Sibin (Frontiers in Plant Science, 2022)
Transmission ratio distortion (TDR) denotes the observed allelic or genotypic frequency deviation from expected Mendelian segregation ratios in offspring of heterozygote. TRD can severely hamper gene flow between and within rice species. Here, we report the fine mapping and characterization of two loci (TDR4.1 and TDR4.2) for TRD using large F2 segregating populations, which are derived from rice chromosome segment substitution lines, each containing a particular genomic segment introduced from the japonica cultivar Nipponbare (NIP) into the indica cultivar Zhenshan (ZS97). The two loci exhibited a preferential transmission of ZS97 alleles in the derived progeny. Reciprocal crossing experiments using near-isogenic lines harboring three different alleles at TDR4.1 suggest that the gene causes male gametic selection. Moreover, transmission bias of TDR4.2 was diminished in heterozygotes when carried homozygous TDR4.1ZS97. This indicates an epistatic interaction between these two loci. TDR4.2 was mapped into a 35-kb region encompassing one candidate gene that is specifically expressed in the reproductive organs in rice. These findings broaden the understanding of the genetic mechanisms of TRD and offer an approach to overcoming the barrier of gene flow between the subspecies in rice, thus facilitating rice improvement by introgression breeding.